Primary and secondary care attendance, anticonvulsant and antidepressant use and psychiatric contact 5–10 years after diagnosis in 188 patients with psychogenic non-epileptic seizures. Issue 9 (20th January 2014) - Duncan, Roderick; Graham, Christopher D; Oto, Maria; Russell, Aline; McKernan, Laura; Copstick, Sue
Abstract : Background and objectives: There have been few studies of long-term outcome in psychogenic non-epileptic seizures (PNES), and none of long-term healthcare utilization. Methods: We studied attendance with seizures, healthcare use and employment over a 6-month period from the family doctors of 260 consecutive patients with psychogenic non-epileptic seizures (PNES), 5–10 years after diagnosis. Results: We obtained clinical data in 188/260 patients (72.3%), of whom 60 (31.9%) had attended primary or secondary care with seizures in the previous 6 months. Predictors of attendance with seizures included a diagnosis of epilepsy+PNES (OR 5.7, p=0.009), work status (OR 3.9, p=0.027) and social security payments (OR 6.3, p=0.003). Latency to diagnosis was not predictive. Emergency admission data were available in 187 patients, of whom 25 (13.4%) had emergency hospital attendances. Prescription data were available for 172 patients, of whom 154 had 'PNES only'. Of these, 17 (11.0%) remained on antiepileptic medication (AED). 68/172 patients (39.5%) were prescribed antidepressant (AD) drugs. We had psychiatric contact data in 185 patients, of whom 49 (26.5%) had accessed psychiatric services in the last 6 months. Conclusions: Surprisingly few of our patients had presented with seizures during the study period. Early reductions in both AED use and healthcare use were sustained long term. Although psychiatric and employment outcomes were less encouraging, some aspects of PNES outcome may be better than previously thought.